MODELLING AND STABILITY ANALYSIS OF GONORRHEA TRANSMISSION MODEL WITH TREATMENT AND CONDOM EFFICACY - SANDA, A.; Y. AJIYA,; B. SAMBO,; S. I. KAMARA, (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
A deterministic gonorrhea model is designed and used to study the dynamics of transmission of gonorrhea disease. The positivity of the solution was determined to be positive with the positive initial data; the invariant region was also determined to be positively invariant. In the absent of disease, the disease free equilibrium point was determined and shown to be both locally and globally asymptotically stable when the associated basic reproduction 0 R , is less than unity .Furthermore, the model has a unique endemic equilibrium point which is locally and globally asymptotically stable, whenever the basic reproduction is greater than unity. Sensitivity analyses and numerical simulation carried out shows that increase in the effective contact rate, which is the most sensitive parameter followed by progression rate from exposed class to the infected class and the relative risk of an infected persons been infective increase the burden of the disease in the community, while increase in condom efficacy, compliance of condom used and treatment of gonorrhea infected individual will reduce the disease burden and so it has a significant impact in controlling gonorrhea transmission in the community.